The anti-miR21 antagomir, a therapeutic tool for colorectal cancer, has a potential synergistic effect by perturbing an angiogenesis-associated miR30 - Song, Min-sun; Rossi, John J. (Frontiers in Genetics, 2014)
Colon cancer has the third highest incidence and mortality among cancers in the United States. MicroRNA-21 (miR21) has been described as an oncomir that is highly overexpressed in tumor tissue from colorectal cancer. Recent studies showed that silencing of miR21 through use of a miR21 inhibitor (anti-miR21) affected viability, apoptosis and the cell cycle in colon cancer cells. We identified an anti-miR21 that targets miR21 to inhibit genes by both post-transcriptional gene silencing (PTGS) and transcriptional gene silencing (TGS) in the cytoplasm and nucleus, respectively. Overexpression of anti-miR21 in colon cancer cells caused changes in miRNA expression levels. We found that treatment with anti-miR21 down-regulated expression of miR30, which is involved in angiogenesis. In an in vitro angiogenesis assay, network formation induced by an angiogenesis activator was reduced upon treatment with anti-miR21. Sequence analysis of anti-miR21 and pri-miR30 revealed homology between anti-miR21 and the 3’ end of pri-miR30, suggesting that anti-miR21 may bind to pri-miR30 and block processing of the miRNA processing. These results suggest anti-miR21 has a role not only in tumor growth but also in angiogenesis. Therefore, treatment with the anti-miR21 antagomir may have a synergistic effect mediated through suppression of miR30.